The Prevalence, Morphological Variations, Familial Traits And Complications Of Tori In Northern Region Of Malaysia - Li, Zhen (2024)
Tori are common non-pathological exogenous tissue in oral cavity, which occasionally produce complications,especiallyaffectingthe constructionand wearing of denture. Tori can be divided into torus palatinus (tp) on the maxilla and torus mandibularis(tm) on the mandible. Its existenceis determinedby bothgenetic and environmental factors.Theobjectives ofthisstudyweretodeterminethedifferences in theprevalenceandmorphologicalvariationsoftoriamongthethreemajorracesand sexes in malaysia. In addition,toexplore the probability of familial traits and complicationsfacedbypatients who havetori. In this study, 779study models were randomlyselected fromthe dental clinicat advancedmedicaland dental institute, usm. The study was divided into two parts: study models examination and questionnaire survey.The prevalenceand morphologicalvariations(size,shape,and location)of torion study modelswere examined,andinformationon familial traits andcomplicationsof havingtoriwasdetermined fromthequestionnairesurvey.The findings showed that prevalenceoftoriwas64.3%, wheretpwas 58.5%andtm was 18.6%. Tp was found more infemales (61.8%) thanmales(50.9%)whiletm was foundmore inmales(26.9%)than females(15%), all were statistically significantly different(ptp-sexes= 0.004, ptm-sexes< 0.001). Thehighestprevalencefor tpwas in malays(60.6%)whiletm was in indians(27.3%),onlytphasstatistical difference among races (ptp-races= 0.001, ptm-races= 0.534).